2022
DOI: 10.3390/plants11233216
|View full text |Cite
|
Sign up to set email alerts
|

The Streptomyces scabiei Pathogenicity Factor Thaxtomin A Induces the Production of Phenolic Compounds in Potato Tubers

Abstract: The phytotoxin thaxtomin A (TA) is the key pathogenicity factor synthesized by the bacteria Streptomyces scabiei, the main causal agent of common scab of potato (Solanum tuberosum L.). TA treatment of potato tuber flesh produces a brown color that was attributed to necrosis. The intensity of TA-induced browning was generally thought to correlate with potato sensitivity to the disease. In this study, we found that TA-induced browning was much more intense in the potato tuber flesh of the common scab moderately … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…While these bacteria form mutualistic relationships with coconut plants and plants in general, protecting them against pathogens through the production of secondary metabolites and activation of the plant's immune system, it is important to note that they can pose some environmental concerns. If not properly managed, the antimicrobial properties of these metabolites can disrupt natural microbial communities and potentially affect beneficial microorganisms (Isayenka & Beaudoin, 2022). Additionally, certain Streptomyces spp.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While these bacteria form mutualistic relationships with coconut plants and plants in general, protecting them against pathogens through the production of secondary metabolites and activation of the plant's immune system, it is important to note that they can pose some environmental concerns. If not properly managed, the antimicrobial properties of these metabolites can disrupt natural microbial communities and potentially affect beneficial microorganisms (Isayenka & Beaudoin, 2022). Additionally, certain Streptomyces spp.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, certain Streptomyces spp. can cause potato scab and produce phytotoxins involved in plant diseases (Isayenka & Beaudoin, 2022; Pandey & Gupta, 2020). Despite reduced microbial diversity in healthy coconut samples, Streptomyces and Nonomuraea genera continued to dominate, suggesting their potential significance in either suppressing diseases or preserving plant health.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, phenolic acids, alkaloids, and flavonoids accounted for the highest percentage of the differential metabolites in each comparison group. Similarly, Isayenka et al [62] found that the phytotoxin thaxtomin A (TA) induced browning of potato tuber flesh due to the accumulation of phenolic compounds, which may play a role in protecting potato tubers from Streptomyces scabiei. In addition, it is possible that because the family of tyrosinederived metabolites is flavonoids, DON induction caused significant downregulation of L-tyrosine, resulting in a reduction of 84% of all flavonoids in DAMs, suggesting that flavonoid levels may be negatively correlated with DON-induced plant defense.…”
Section: Discussionmentioning
confidence: 99%